AWARENESS OF MENSTRUAL HYGIENE PRACTICES AMONG ADOLESCENTS IN URBAN AND RURAL AREAS: A COMPARATIVE ANALYSIS - Thakur, Sarima; Suri, Chanchal Sachdeva; Ms. Manorama; Rai, Dr. Gayatri; Verma, Dr Amit (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The present research has mentioned the provision of menstrual hygiene products and menstrual hygiene-related awareness that will certainly provide a deeper insight into the menstrual hygiene practices. The paper conducts a comparative study of both rural and urban population to determine the contribution of awareness to accessibility to menstrual hygiene products. The awareness and access correlation was tested with the help of such statistical analysis as chi-square, t-tests, and regression analysis. The results are that there are gigantic diversities in the rural and urban location of the awareness phase of the respondents, the consciousness of the menstrual hygiene, and the procurement of the hygiene products. The results of regression analysis show that accessibility can be explained by 34.4 percent of knowledge and awareness, which indicates that both are important predictors of access to menstrual hygiene products. The findings imply that access to menstrual health education and behaviour can be increased by providing better access, especially in rural regions. The paper highlights the importance of specific educational behaviour interventions and the enhancement of infrastructure to attain better menstrual health outcomes and general wellbeing of women and adolescent girls.